Pharmacogenetic evidence that cd36 is a key determinant of the metabolic effects of pioglitazone - Qi, N; Kazdová, Ludmila; Zídek, Václav; Landa, Vladimír; Křen, Vladimír; Pershadsingh, HA; Lezin, ES; Abumrad, NA; Pravenec, Michal; Kurtz, TW (The Journal of biological chemistry, 2002)
Pioglitazone, like other thiazolidinediones, is an insulin-sensitizing agent that activates the peroxisome proliferator-activated receptor gamma and influences the expression of multiple genes involved in carbohydrate and lipid metabolism. However, it is unknown which of these many target genes play primary roles in determining the antidiabetic and hypolipidemic effects of thiazolidinediones. To specifically investigate the role of the Cd36 fatty acid transporter gene in the insulin-sensitizing actions of thiazolidinediones, we studied the metabolic effects of pioglitazone in spontaneously hypertensive rats (SHR) that harbor a deletion mutation in Cd36 in comparison to congenic and transgenic strains of SHR that express wild-type Cd36. In congenic and transgenic SHR with wild-type Cd36, administration of pioglitazone was associated with significantly lower circulating levels of fatty acids, triglycerides, and insulin as well as lower hepatic triglyceride levels and epididymal fat pad weights than in SHR harboring mutant Cd36. Additionally, insulin-stimulated glucose oxidation in isolated soleus muscle was significantly augmented in pioglitazone-fed rats with wild-type Cd36 versus those with mutant Cd36. The Cd36 genotype had no effect on pioglitazone-induced changes in blood pressure. These findings provide direct pharmacogenetic evidence that in the SHR model, Cd36 is a key determinant of the insulin-sensitizing actions of a thiazolidinedione ligand of peroxisome proliferator-activated receptor gamma.
Keywords: Sequence Deletion; Pharmacogenetics; DNA Primers; přenašeče organických aniontů; inzulinová rezistence; Glucose; sekvenční delece; farmakogenetika; CD36 Antigens; Thiazolidinediones; DNA primery; zvířata; Rats; Rats, Inbred SHR; membránové glykoproteiny; Base Sequence; potkani inbrední SHR; thiazolidindiony; Insulin Resistance; glukosa; thiazoly; sekvence nukleotidů; Organic Anion Transporters; Blotting, Northern; northern blotting; Insulin; krysa rodu Rattus; Membrane Glycoproteins; hypoglykemika; Animals; inzulin; kosterní svaly; Thiazoles; Hypoglycemic Agents; Muscle, Skeletal; antigeny CD36